THE INDIS STYLE: THE TRANSFORMATION AND HYBRIDIZATION OF BUILDING CULTURE IN COLONIAL JAVA INDONESIA (Paramita: Historical Studies Journal, 2018)
This historical study is focused on Indis style houses and buildings in Java during colonial period. The study discusses the reception and adaptation of Dutch and other cultures together with the local cultures in the transformation and hybridization of Indonesian architectural design production and reproduction. The study concludes that Indis style is a proof for the western inability to avoid the social and cultural influence of the locals, representations of new hybrid identities who want to show themselves as closer to the west and distance from theÂ  indigenous, representation of new identity among those who found a new definite motherland since others consider themselves alien, symbol of modernity for those who were looking for a new social status and justify their existence, and a representation of the history of colonialism itself.Â Kajian sejarah ini difokuskan pada rumah dan bangunan bergaya Indis di Jawa pada masa kolonial. Tulisan ini mendiskusikan tentang resepsi dan adaptasi budaya Belanda dan budaya lainnya bersama-sama budaya tempatan dalam transformasi dan hibridisasi pada proses produksi dan reproduksi desain arsitektur Indonesia. Kajian ini menyimpulkan bahwa gaya Indis merupakan bukti dari ketidakmampuan Barat untuk menghindar dari pengaruh sosial dan kebudayaan tempatan, representasi dari identitas hibrid baru yang ingin menunjukkan dirinya lebih dekat kepada Barat namun berjarak dari penduduk asli, representas dari identitas baru bagi mereka yang menemukan ibu pertiwi yang baru ketika kelompok lain menganggap mereka sebagai orang asing, simbol modernitas bagi mereka yang sedang mencari status sosial baru serta untuk menjustifikasi keberadaannya, dan sekaligus representasi dari sejarah kolonialisme itu sendiri.Â